A Content Analysis of the English Textbook “English for Nusantara” for the Eighth Grade of Junior High School Based on Brian Tomlinson’s Theory - Lase, Ertaniat; Laoli, Adieli; Waruwu, Yaredi; Harefa, Afore Tahir (Universitas Muhammadiyah Barru, 2026)
This study examines the importance of high-quality teaching materials, particularly textbooks, in achieving English language learning objectives in Indonesia. Textbooks play a crucial role in the Merdeka Curriculum. Therefore, this study aims to analyze the feasibility of the English textbook “English for Nusantara” for eighth-grade junior high school students at SMP Negeri 1 Gunungsitoli Barat, by evaluating its content against Brian Tomlinson's 16 criteria for teaching materials. Employing a Qualitative approach with content analysis on Chapters 1-5, the findings revealed that the textbook substantially meets the criteria, with 14 criteria fulfilled and a high match percentage of 87.5%, placing it in the